Evaluation of Entrepreneurship-Based Link and Match Program with CIPP Model for Vocational High School Students: Legal Communication Study - Desy Ariani; Mesiono; Mardianto (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The link and match program is designed to bridge the gap between the world of education and the world of work through the development of children's entrepreneurial competencies. This study aims to determine the planning, implementation, supervision, and evaluation of the entrepreneurship-based link and match program at TKIT Insan Adzkia Marelan. The place or location of this research is at TKIT Insan Adzkia Marelan located in Tanah Enam Ratus, Kec. Medan Marelan, Medan City, North Sumatra. The research was conducted for five months starting from August 5, 2024-December 20, 2024. This study used a qualitative method with the research subjects being the principal and teachers. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. Data analysis was carried out through data reduction, data presentation, as well as drawing conclusions and verification. The results of the study showed that program planning includes entrepreneurship development, theoretical and practical learning, improving soft skills, and expanding networks with the business world. Program implementation is carried out through curriculum integration, mentoring of teachers and industry partners, project-based learning, internships, and competency certification. Supervision is carried out with the right methods, technology-based monitoring, and collaboration with industry partners. Evaluation of the link and match program: Ensuring the effectiveness of the program from the government and the industrial world, identifying the strengths and weaknesses of the program, improving program implementation, strengthening relations with DU/DI, absorption of graduates into DU/DI, evaluation of all link and match programs.